Van earthquakes (23 October 2011 and 9 November 2011) and performance of masonry and adobe structures - Guney, D. (COPERNICUS GESELLSCHAFT MBH, 2012)
Earthquakes, which are unavoidable natural phenomena in Turkey, have often produced economic and social disaster. The latest destructive earthquakes happened in Van city. Van, Turkey, earthquakes with M = 7.2 occurred on 23 October 2011 at 13:41 (local time), whose epicenter was about 16 km north of Van (Tabanlivillage) and M = 5.6 on 9 November 2011 epicentered near the town of Edremit south of Van in eastern Turkey and caused the loss of life and heavy damages. Both earthquakes killed 644 people and 2608 people were injured. Approximately 4000 buildings collapsed or were seriously damaged. The majority of the damaged structures were seismically insufficient, unreinforced masonry and adobe buildings in rural areas. In this paper, site surveys of the damaged masonry and adobe buildings are presented and the reasons for the caused damages are discussed in detail.
Keywords: Geology; Meteorology & Atmospheric Sciences; Water Resources